2019
DOI: 10.3390/genes10110857
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chromosome Mapping of Musk Ox and the X Chromosome among Some Bovidae Species

Abstract: Bovidae, the largest family in Pecora infraorder, are characterized by a striking variability in diploid number of chromosomes between species and among individuals within a species. The bovid X chromosome is also remarkably variable, with several morphological types in the family. Here we built a detailed chromosome map of musk ox (Ovibos moschatus), a relic species originating from Pleistocene megafauna, with dromedary and human probes using chromosome painting. We trace chromosomal rearrangements during Bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 48 publications
(103 reference statements)
2
18
0
Order By: Relevance
“…Although there was no indication of any prevailing type of rearrangements between groups, the results showed that X chromosomes of voles, not only of the genus Microtus, frequently undergo intrachromosomal rearrangements. Such high variability in X chromosome morphology generated by intrachromosomal rearrangements was previously documented only for some ruminants 11,12 . As for arvicoline rodents, ruminants are also characterized by an increased rate of karyotype evolution among mammals.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although there was no indication of any prevailing type of rearrangements between groups, the results showed that X chromosomes of voles, not only of the genus Microtus, frequently undergo intrachromosomal rearrangements. Such high variability in X chromosome morphology generated by intrachromosomal rearrangements was previously documented only for some ruminants 11,12 . As for arvicoline rodents, ruminants are also characterized by an increased rate of karyotype evolution among mammals.…”
Section: Discussionmentioning
confidence: 88%
“…However, there are well known cases when the X chromosome, both with respect to gene content and marker order 10 , is not conserved. The X chromosomes of a significant number of mouse-like rodents (Myomorpha) and cetartiodactyls are clearly rearranged and subject to both intrachromosomal and interchromosomal rearrangements [11][12][13][14] . The reasons why some taxa escape X chromosome conservatism are not clear.…”
mentioning
confidence: 99%
“…The Robertsonian translocation (rob) has been the most common chromosomal mechanism characterizing the evolutionary history of many autosome chromosomes from bovid species. Still, complex chromosome rearrangements are also followed by sex chromosomes [ 36 , 57 ].…”
Section: Evolutionary Cytogeneticsmentioning
confidence: 99%
“…These chromosome changes have been the result of karyotype evolution, determining several species. Furthermore, the study of chromosomes has been mainly used in animal cytogenetics to (1) verify the relationship between chromosome abnormalities and fertility [ 3 , 4 , 5 , 6 , 7 ]; (2) physically map both type I (expressed sequences) and type II (SSRs, microsatellite marker, STSs) loci, especially using fluorescence in situ hybridization (FISH) techniques [ 8 , 9 , 10 , 11 , 12 ]; (3) correctly identify the chromosomes involved in chromosomal abnormalities via chromosome banding techniques [ 13 , 14 ]; (4) reveal chromosome rearrangements occurring in some chromosomal abnormalities, especially using both FISH mapping [ 15 , 16 , 17 ] and comparative genome hybridization array (aCGH) techniques [ 18 , 19 ]; (5) compare related and unrelated genomes by using the Zoo-FISH technique [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], centromeric SAT sequences by FISH mapping [ 29 ], or detailed FISH mapping along chromosomes [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]; and (6) test the genome stability of several bovids, including the river buffalo, with both in vitro and in vivo (natural) exposure to potential mutagens [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], or affected by limb malformation...…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the authors provide a comprehensive view of this species combining conventional and molecular cytogenetic methods, single chromosome DNA sequencing, and breeding experiments, revealing the chromosome segregation pattern as well as the reproductive performance of different karyomorphs. Finally, Proskuryakova et al [28] illustrate how, by comparative chromosome mapping, it is possible to identify variations in the X chromosome structure of four bovid species: nilgai bull (Boselaphus tragocamelus), saola (Pseudoryx nghetinhensis), gaur (Bos gaurus), and Kirk's Dikdik (Madoqua kirkii).…”
mentioning
confidence: 99%